2019
DOI: 10.1021/jacs.9b07253
|View full text |Cite
|
Sign up to set email alerts
|

Ni-Catalyzed Enantioselective Intermolecular Hydroamination of Branched 1,3-Dienes Using Primary Aliphatic Amines

Abstract: A Ni-catalyzed intermolecular enantioselective hydroamination of branched 1,3-dienes is reported. The method is broadly applicable, highly regio-, chemo-, and enantioselective, and provides direct access to valuable chiral allylic amines starting from linear or α-branched aliphatic primary amines or secondary amines. Mechanistic studies have been conducted using 31P NMR spectroscopy for reaction progress monitoring, isotopic labeling experiments (2H), and kinetic analysis. The resting state of the catalyst is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 73 publications
0
36
1
Order By: Relevance
“…These findings strongly suggested that a reversibility of carbon-nitrogen bond formation was involved in this reaction. These results are in consistence with Hartwig's results (Pawlas et al., 2002) but inconsistent with the results of Mazet's conditions (Tran et al., 2019).
Scheme 1Amine Exchange Experiment(1) Exchange experiment of secondary amine-based product (3t) with secondary amine (morpholine).(2) Exchange experiment of secondary amine-based product (3t) with primary amine (furfuryl amine).(3) Exchange experiment of primary amine-based product (3k) with secondary amine (morpholine).(4) Exchange experiment of primary amine-based product (3k) with primary amine (furfuryl amine).Data are represented as mean value of three times; see also Scheme S5.
…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…These findings strongly suggested that a reversibility of carbon-nitrogen bond formation was involved in this reaction. These results are in consistence with Hartwig's results (Pawlas et al., 2002) but inconsistent with the results of Mazet's conditions (Tran et al., 2019).
Scheme 1Amine Exchange Experiment(1) Exchange experiment of secondary amine-based product (3t) with secondary amine (morpholine).(2) Exchange experiment of secondary amine-based product (3t) with primary amine (furfuryl amine).(3) Exchange experiment of primary amine-based product (3k) with secondary amine (morpholine).(4) Exchange experiment of primary amine-based product (3k) with primary amine (furfuryl amine).Data are represented as mean value of three times; see also Scheme S5.
…”
Section: Discussioncontrasting
confidence: 87%
“…Chiral centers are generally induced via a carbon-carbon bond-forming process, involving the direct oxidative addition of C-H bonds (Cai et al., 2019, Cheng et al., 2018, Cheng et al., 2019, Diesel et al., 2018, Diesel et al., 2019, Donets and Cramer, 2013, Li et al., 2019a, Lv et al., 2018, Woźniak and Cramer, 2019, Zhang et al., 2019) or an external stoichiometric reductant, such as alcohol (Chen et al., 2019) or hydrosiloxane (Ahlin and Cramer, 2016). However, nickel-catalyzed asymmetric hydrofunctionalization of unsaturated compounds involving a carbon-heteroatom bond formation has not been studied much (Tran et al., 2019). As an extension of our studies with nickel-catalyzed carbon-carbon bond formations (Li et al., 2019b, Wang et al., 2019), we turned our attention to carbon-heteroatom bonds.…”
Section: Introductionmentioning
confidence: 99%
“…3 ) and vehicles ( wax‐1 vs . TMSC‐1 ) may have not only on reactivity but also on regio‐ and enantioselectivity [26] . Quite surprisingly, these aspects have not been addressed in related comparative studies where focus was placed exclusively on reactivity ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Early studies have demonstrated the ability of Ni-based system to catalytically promote the hydroamination of 1,3-dienes [106][107][108]. In 2019, inspired by the work of Hartwig on cyclic dienes [105], the group of Mazet reported a regio-and enantioselective Nicatalyzed intermolecular hydroamination of 2-substituted 1,3-dienes with primary and secondary amines under mild conditions using a catalytic combination of Ni(COD) 2 and enantiopure biphosphine (R,R)-BenzP* ligand and trifluoroethanol (TFE) as an additive (Figure 18, top) [109]. The method is broadly applicable, highly regio-, chemo-, and enantioselective for 2-(hetero)aryl-substituted 1,3-dienes and primary amines, and provides direct access to valuable enantioenriched allylic secondary amines by selective 3,4-addition.…”
Section: Hydroaminationmentioning
confidence: 99%